Superficial vein thrombosis in a child with methylene tetrahydrofolate reductase (MTHFR) heterozygous mutation: a case report - Twanabasu, Sajal; Shrestha, Kipa; Das, Sunil Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Methylene Tetrahydrofolate reductase (MTHFR) mutation leads to increased plasma homocysteine levels which is associated with increased risk of thrombosis. MTHFR mutation might be one of the unusual cause of thrombosis besides the usual risk factors like trauma, venous procedures, surgery, malignancy and immobility. We report a case of 13 years old male presenting with superficial venous thrombosis in bilateral forearm who later on evaluation was found to have heterozygous Methylene Tetrahydrofolate Reductase (MTHFR) mutation.